Human papillomavirus vaccination and Pap test uptake, awareness, and barriers among young adults in Gulf Cooperation Council countries: A comparative cross-sectional survey - Ibrahim Mahmoud; Mithaq Mohammed A Al Eid; Meera Ahmed Mohamed; Ahmad Jehad Aladwani; Nagwa El Mustafa El Amin (Elsevier, 2024)
Background: Human papillomavirus (HPV) vaccination and Pap tests are recognized as effective preventive measures to reduce the incidence of HPV-related diseases among young adults. The objective of this study was to assess HPV vaccination and Pap test uptake, awareness, and barriers among young adults in the Gulf Cooperation Council (GCC) countries, including Bahrain, Kuwait, Oman, Qatar, the Kingdom of Saudi Arabia (KSA), and the United Arab Emirates (UAE). Methods: A comparative cross-sectional study was conducted from January to April 2024, involving 831 young adults aged 18-39 residing in GCC countries. The main outcome measures were HPV vaccination and Pap test uptake rates, awareness of the HPV vaccine and Pap testing, and barriers to vaccination. Data were collected using online platforms. The Chi-square test and Fisher's exact test were used for data analysis. Results: The UAE had the highest vaccination rate at 18.9% (50/264), followed by Qatar at 5.8% (6/104), and KSA at 4.6% (10/216), p < 0.001. Individuals with health insurance had higher vaccination rates than those without (11% vs. 5.4%, p = 0.006). Awareness of the HPV vaccine was highest in the UAE (49.6%) and KSA (58.8%), while awareness of Pap smear testing among females was similarly high in these countries (62.4% and 65.9%, respectively). However, actual Pap smear testing rates were highest in Bahrain (15.9%) and Qatar (13.4%). The main barriers to vaccination cited by participants were lack of knowledge (53.6%) and the absence of medical recommendations (13.2%). Conclusion: The study's findings suggest the need of targeted educational campaigns to increase HPV vaccine uptake among both genders and Pap test participation among females. Additionally, incorporating HPV screening and vaccination into routine national programs in GCC countries and emphasising the crucial role of healthcare providers in influencing vaccination decisions are recommended strategies.